Influence of crystallization temperature on physical and chemical properties of BiFeO3 thin films - Teixeira, Marco Antonio de Mello [UNESP] (2025)
The objective of this study is to establish synthesis protocols for bismuth ferrite thin films, with a particular focus on crystallization temperature, and to evaluate the influence of these protocols on the final properties of the films. A direct correlation was identified between the selected crystallization temperatures and the formation of various types and concentrations of defects, which, in turn, modulate these properties. Our findings indicate that, within the studied temperature range, 600 °C is the ideal crystallization temperature for obtaining films with minimized defects and enhanced functional properties. The sample crystallized at this temperature exhibited a significant reduction in point -free and complex - and secondary phase defects, leading to superior performance compared to the other samples. Specifically, this sample demonstrated the lowest electrical conductivity and leakage current values, the highest percentage increase in electrical conductivity and current under green light illumination, and the highest electrical polarization values.